2002
DOI: 10.1108/08876040210436902
|View full text |Cite
|
Sign up to set email alerts
|

Selecting and promoting service encounter elements in passenger rail transportation

Abstract: A critical issue in the effective development and promotion of services is the identification of which service components are most closely related to attitude toward the service provider and repeat purchase behavior. The present study disaggregates a service (passenger rail transportation) into pre‐core and core service performances, and uses these elements to create a model of the effects on relevant service attitudes and intentions. Using a sample of 2,529 Amtrak riders, the present research finds that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…They are similar to most of the attributes used in other rail passenger studies, e.g. Hanna and Drea (1998), Drea and Hanna (2000), and Tripp and Drea (2002) that used literature searches and focus groups. Their Cronbach alpha values are similar to those in this study.…”
Section: Conclusion and Recommendationsmentioning
confidence: 91%
See 1 more Smart Citation
“…They are similar to most of the attributes used in other rail passenger studies, e.g. Hanna and Drea (1998), Drea and Hanna (2000), and Tripp and Drea (2002) that used literature searches and focus groups. Their Cronbach alpha values are similar to those in this study.…”
Section: Conclusion and Recommendationsmentioning
confidence: 91%
“…In the later paper cost, convenience getting to the station, parking availability, Amtrak comfort, seat comfort, ride, seating area cleanliness, and courtesy of on-board staff were the service quality attributes tested. Tripp and Drea (2002) also used a survey of Amtrak passengers to assess the "direct and indirect relationship between pre-core/peripheral and core service performance components and their impact on the likelihood of repeat purchase" (p. 433). They found that the core experiences on-board that determined the customer's attitude to the service provider an subsequently their intention to use the train again.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research on service quality analyses In recent years, the management of service quality has attracted considerable attention from academics who have investigated the characteristics of service quality (e.g., Golder et al 2012;Harvey 1998), the effect of service quality on behavioral intentions (e.g., Tripp and Drea 2002;Sánchez Pérez et al 2007), and the impact of service quality on operational and business performance (e.g., Adam 1994). Consequently, public transport operators as well as other service providers have begun to use quality measures for various quality management purposes.…”
Section: Measurement and Analyses Of Service Qualitymentioning
confidence: 99%
“…In recent years, the management of public transport quality has attracted considerable attention from academics investigating the measurement of service quality (Prioni and Hensher 2000;, the effect of service quality on behavioral intentions (e.g., Tripp and Drea 2002;Sánchez Pérez et al 2007), or the design of performance-based quality contracts (Hensher and Stanley 2003;Hensher and Houghton 2004). Likewise, public transport operators are increasingly focusing on improving service quality, assuming that this has an impact on their performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, when customers evaluate the quality of a service as a whole, some service attributes are considered more important than others (Mokonyama and Venter, 2013), being their influence implicitly taken into account with their global evaluation. Therefore, there are several categories of attributes having a greater or lesser impact on service quality (de Oña et al, 2013;Eboli and Mazzulla, 2012;TRB, 2004;Tripp and Drea, 2002); their influence should be considered when an indicator of the level of quality is calculated.…”
Section: Introductionmentioning
confidence: 99%